Roles of multimodality imaging in rare neuromuscular and neurodegenerative diseases - Mamdouh Ali, Bayan; Alturk, Hesham Idriss; Alharbi, Amjad Hamdan; Alamer, Abdallah Jafar; Alqahtani, Khalid Mesfer; Mahrous, Leena M. Al; Allehyani, Lujain Marzouq; Slais, Fatimah Radi; Arishi, Nouriyah Haider; Qasem, Alshaima Abdh; Aljughiman, Abdullah Khalid (International Journal Of Community Medicine And Public Health, 2025)
Physicians face challenges in diagnosing and managing of neuromuscular and neurodegenerative diseases, such as amyotrophic lateral sclerosis and Huntington’s disease, as they are rare, clinically variable, and often misdiagnosed by traditional diagnostic methods. To overcome these challenges, multimodality imaging, combining techniques like magnetic resonance imaging (MRI), computed tomography (CT), positron emission tomography (PET), and ultrasound, has emerged to provide complementary structural, functional, and molecular data. This review discusses the roles of multimodality imaging in diagnosing, monitoring, and managing these rare diseases. Structural changes and neural connectivity are identified by MRI, and metabolic and molecular abnormalities are detected by PET. Real time evaluation of nerve and muscle abnormalities is provided by ultrasound, whereas CT aids in evaluation of respiratory function and skeletal structures. These methods are combined to improve diagnostic accuracy and to provide further understanding of disease mechanisms. Emerging multimodal imaging techniques, such as ultra-high-field MRI and hybrid PET-MRI systems, are being developed to provide greater resolution and efficiency. Multimodality imaging is a critical tool in improving the care of patients with rare neuromuscular and neurodegenerative disorders. However, its widespread use is hindered by high costs, limited access, and the need for standardized protocols and validation. Future directions include the development of imaging biomarkers, integration with other diagnostic methods, and the use of artificial intelligence to analyze complex imaging data.